PERAN PEMERINTAH NAGARI DALAM PENGELOLAAN WISATA RELIGI IKAN LARANGAN LUBUK LANDUR KABUPATEN PASAMAN BARAT MENURUT PERSPEKTIS ISLAM - Mulia Vandini; Gusril Basir (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The role of the Government in the management of the Lubuk Landur Prohibited Fish Religious Tourism in West Pasaman Regency highlights the importance of the government's role in motivating the community and the private sector to participate in the development of religious tourism destinations. The management of religious tourism requires a significant role of the government, especially in the implementation of DSN/MUI fatwa Number 108/DSN/MUI/X/2016. This management is based on sharia principles that lead to public benefits, cleanliness, nature preservation, worship facilities that meet sharia requirements, and avoidance from prohibited acts such as immorality, adultery, and drugs. West Pasaman has interesting tourism potential such as prohibited fish tourism, which is part of the tradition of the Minangkabau people. However, there was a decrease in tourist visits in 2019 in Lubuk Lundur, due to the lack of trust in the private sector in the role of the government in the management of religious tourism. This causes tourists to violate Islamic sharia rules, triggers distrust in the private sector, and the lack of cooperation with the government and the Lubuk Landur nagari government in the management of prohibited fish religious tourism shows efforts to embrace the private sector, empower the community, and establish cooperation. Despite the obstacles in direction and control, the nagari government has shown positive developments. Through the role of coordinators, facilitators, regulators, motivators. The purpose of this study is to analyze the role of the nagari government in the management of religious tourism of prohibited lubuk landur fish in West Pasaman Regency according to an Islamic perspective using qualitative methods. The results of this study show that the role of the nagari government affects the management of religious tourism of fish prohibited in Lubuk Landur West Pasaman Regency according to the Islamic perspective. The role of the government coordinator aims to embrace the community in development, the role of the facilitator to create conducive conditions, the role of the stimulator to create a strategy for tourist attractions, and the role of the motivator to ensure the continuity of the tourism business. Thus, the role of the Lubuk Landur nagari government in the management of prohibited fish religious tourism shows success in embracing all components of society, empowering local potential, and maintaining the sustainability of religious tourism in accordance with Islamic sharia principles.